Analisis Penerapan PSAK No. 115 Tentang Pengakuan Pendapatan Studi Kasus PT. SEISHIN ABYAKTA SOLUSINDO - Fauzan, Muhammad Nur; Sudarta, M Imam; Hurriyaturrohman, Hurriyaturrohman; Indupurnahayu, Indupurnahayu (JURNAL PUNDI, 2025)
This study aims to evaluate the implementation of PSAK No. 115 (based on IFRS 15) in revenue recognition for the construction project of EP1 Apartment Building Structure in Mayville Cikarang, carried out by PT Seishin Abbyakta Solusindo. The specific objective is to assess whether the company has properly applied PSAK No. 115 in terms of revenue recognition, revenue measurement, transaction recording, and revenue disclosure in accordance with the applicable accounting standards. The research uses a qualitative approach with data collection techniques including observation, semi-structured interviews, and documentation. The collected data is analyzed descriptively to identify the alignment of PSAK No. 115 implementation within the company’s accounting practices. The results indicate that the company has accurately applied PSAK No. 115 across all stages of revenue recognition—from contract identification and performance obligations to measurement, recording, and disclosure. Revenue is recognized over time based on physical progress, in accordance with the percentage of completion method. There are no contract combinations or modifications affecting revenue recognition. The transaction price of IDR 22,000,000,000 is allocated to a single performance obligation, and project costs are recorded proportionally to physical progress. Revenue disclosures have also been made in compliance with the standards, including the recognition of retention and contract liabilities. Therefore, the implementation of PSAK No. 115 by PT Seishin Abbyakta Solusindo is in accordance with the applicable accounting standards, covering all aspects of revenue recognition, measurement, recording, and disclosure for construction contracts.